2022
DOI: 10.1186/s12906-022-03619-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-nociceptive effects of Cinnamon and Clove essential oils nanogels: an in vivo study

Abstract: Background Cinnamon (Cinnamomum zeylanicum) and Clove (Syzygium aromaticum) essential oils are two medicinally important plant-derived substances with a wide range of biological properties. Besides, nanoemulsion-based gels have been widely used to increase topical drug delivery and effectiveness. Methods This study aimed to explore the anti-inflammatory effect (paw edema test) and the anti-nociceptive effect (hot plate and formalin test) of nanoemu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 56 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…Pharmacological studies have demonstrated that eugenol is an effective free radical scavenger with anticonvulsant, bactericidal, antifungal, analgesic, antiseptic, hepatoprotective, and antioxidant properties. The mechanism of eugenol’s anti-inflammatory action involves the inhibition of tumour necrosis factor α (TNF-α) and reduced production of nitrous oxide radicals [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies have demonstrated that eugenol is an effective free radical scavenger with anticonvulsant, bactericidal, antifungal, analgesic, antiseptic, hepatoprotective, and antioxidant properties. The mechanism of eugenol’s anti-inflammatory action involves the inhibition of tumour necrosis factor α (TNF-α) and reduced production of nitrous oxide radicals [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…DLS is routinely observed in NE papers (Azami et al, 2018;Esmaeili, Zahmatkeshan, et al, 2022;Firooziyan et al, 2021). However, several factors may influence the accuracy of the method.…”
Section: Characterizationmentioning
confidence: 99%
“…In addition to the characterization methods mentioned, some methods have been employed occasionally. For example, Fourier‐transform infrared spectroscopy (FTIR) could be used to determine the interactions between the drug loaded and other excipients (Esmaeili, Zahmatkeshan, et al, 2022; Moghaddasi et al, 2018). Differential scanning calorimetry (DSC) has also been carried out to study the possible effect of the active pharmaceutical ingredient (API) on other excipients of the NE (Gué et al, 2016).…”
Section: Characterizationmentioning
confidence: 99%
“…Its bark, commonly known as cinnamon, has a unique fragrance and flavor. Modern pharmacological studies have demonstrated that CJ has various biological activities, including antioxidant, anticancer [ 12 ], and anti-inflammatory effects [ 13 ]. However, most studies have confirmed the efficacy of CJ water extracts but not that of its other extracts.…”
Section: Introductionmentioning
confidence: 99%